2010
DOI: 10.1080/13691058.2010.500398
|View full text |Cite
|
Sign up to set email alerts
|

South African teachers' responses to teenage pregnancy and teenage mothers in schools

Abstract: South African law forbids excluding pregnant teenagers from school and permits young parents to continue with their schooling. However, the existence of progressive policy and law does not by itself ensure that pregnant teenagers and young parents remain in school or experience as little disruption to their studies as possible. Two of the factors influencing the experiences that pregnant girls and young parents have are the attitudes and practices of teachers. We explore how teachers in diverse South African s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 15 publications
8
54
0
1
Order By: Relevance
“…This extract highlights the policing of gender at school that has been widely reported and theorized, 22,23 with the notion of the man as head of the household being equated with sexual dominance.…”
Section: Challenging Gender Norms Within Diverse Cultural Contextsmentioning
confidence: 90%
“…This extract highlights the policing of gender at school that has been widely reported and theorized, 22,23 with the notion of the man as head of the household being equated with sexual dominance.…”
Section: Challenging Gender Norms Within Diverse Cultural Contextsmentioning
confidence: 90%
“…Newspapers, which Oosthuizen (2012) and Daku, Gibbs and Heyman (2012) regard as important sources of knowledge for the general public and policy makers, reported frequently about pregnant learners in all nine provinces of the country (The Mercury 2012:14;Cape Times 2012:1;The Mail and Guardian 2012:23). Unlike in the past when pregnant learners were expelled from schools, these days the Department of Basic Education encourages them to continue attending and forbids school governing bodies from expelling these learners so that they are not further disadvantaged by lack of education (Department of Education, 2007;Bhana, Morrell, Shefer and Ngabaza, 2010). This then leads to a disturbing presence of pregnant learners at secondary school premises as secondary schools cannot adequately provide for their health needs.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in their communities and their schools early pregnancy and young motherhood continue to be stigmatised. 22 In some cases, this is aggravated by being deserted by their baby's father. 23 In contrast, the presence of family support, financial and practical, plays a key role in shaping a more positive and successful outcome in the experience of school-going mothers.…”
mentioning
confidence: 99%
“…12 Research has shown that while some educators are willing to assist pregnant learners, they are hindered by their own attitudes, lack of skills and clear enough guidance on how to do so. 13 Schools reportedly continue to engage in exclusionary practices by creating a hostile environment, forcing some pregnant adolescents out of school, 2,14 thereby denying their constitutional right to education. In this context of unclarity, together with continued moralistic and negative responses to young pregnancy and parenting, young women's equal right to education may be undermined.…”
mentioning
confidence: 99%
See 1 more Smart Citation